Coagulation functions and factors correlated with central nervous system infection in herpes zoster patients - Yuan, Yanrong; Gu, Jing; Liu, Huili; Wang, Yu; Sun, Zeyu; Pan, Dongli; Yan, Yongxing (Frontiers in Immunology, 2025)
ObjectiveReports on central nervous system (CNS) infection caused by varicella-zoster virus (VZV) reactivation are increasing, but its pathogenesis remains unclear, which causes delayed diagnosis and treatment. Some studies suggested that hypercoagulability is involved in the pathogenesis of CNS infection of VZV. This study investigated the coagulation parameters of herpes zoster (HZ) and their correlations with the VZV-related CNS infection, and provided a reference for the early diagnosis and treatment.MethodsWe selected 123 consecutive patients, including 95 HZ cases and 28 VZV meningitis (VZVM) cases hospitalized due to HZ. Forty-seven patients who underwent physical examination in our hospital were used as Health controls (HCs) group. The coagulation parameters of the three groups were measured and compared, and the correlation between coagulation function parameters and CNS infection was analyzed by Logistic regression. the expression of coagulation factor in cerebrospinal fluid (CSF) proteomics of 28 VZVM patients and 11 HZ patients were analyzed.ResultsCompared with HCs group, plasma Fibrinogen (Fib) and D-dimer (DD) levels in HZ and VZVM group were significantly increased (P <0.01), while there were no significant differences in other parameters (P > 0.05). There was also no significant difference in the levels of coagulation parameters between the HZ and VZVM groups (P > 0.05). Proteomic analysis of CSF revealed that there was no difference in the expression levels of Fib, Antithrombin III (AT-III), and coagulation factors VII, IX, X, XI in the HZ and VZVM patients (P > 0.05). The expression levels of coagulation factors XII and XIIIa were higher in VZVM patients than those in HZ patients (P < 0.05 and P < 0.01, respectively).ConclusionIn HZ and VZVM patients, a hypercoagulable state was observed with increased Fib and DD levels. However, hypercoagulation was not a risk factor for CNS infection, and there was no significant correlation between the elevated level and the severity of disease.